SaPI mutations affecting replication and transfer and enabling autonomous replication in the absence of helper phage - Ubeda, Carles; Maiques, Elisa; Barry, Peter; Matthews, Avery; Tormo-Mas, María A.; Lasa, Inigo; Novick, Richard P.; Penadés, José R. (2017)
The SaPIs are chromosomal islands in staphylococci and other Gram-positive bacteria that carry genes for superantigens, virulence factors, resistance and certain metabolic functions. They have intimate relationships with certain temperate phages involving phage-induced excision, replication and efficient packaging in special small-headed infective phage-like particles, resulting in very high transfer frequencies. They generally contain 18-22 ORFs. We have systematically inactivated each of these ORFs and determined their functional groupings. In other reports, we have shown that five are involved in excision/integration, replication and packaging. In this report, we summarize the mutational analysis and focus on two key ORFs involved in regulation of the SaPI excision-replication-packaging cycle vis-a-vis phage induction. These two genes are divergently transcribed and define the major transcriptional organization of the SaPI genome. One of them, stl, encodes a master repressor, possibly analogous to the standard cI phage repressor. Mutational inactivation of this gene results in SaPI excision and replication in the absence of any inducing phage. This replicated SaPI DNA is not packaged; however, since the capsid components are provided by the helper phage. We have not yet ascertained any specific function for the second putative regulatory gene, though it is highly conserved among the SaPIs.